Understanding by Communication. - Borisova, Elena (Cambridge Scholars Publishing, 2013)
This volume features current linguistic theories and focuses on understanding in communication, elaborated in modern Russian linguistics. What makes the volume unique is that it offers ideas which accentuate the paradigms that significantly differ from those which are in the focus of, or being cultivated in, European linguistic schools or American grammatical traditions. The volume is intended as a comprehensive introduction to East European linguistic thought, which will be interesting to We ...